2018
DOI: 10.1016/j.jcss.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Pebbling meets coloring: Reversible pebble game on trees

Abstract: The reversible pebble game is a combinatorial game played on rooted DAGs. This game was introduced by Bennett [1] motivated by applications in designing space efficient reversible algorithms. Recently, Siu Man Chan [2] showed that the reversible pebble game number of any DAG is the same as its Dymond-Tompa pebble number and Raz-Mckenzie pebble number.We show, as our main result, that for any rooted directed tree T , its reversible pebble game number is always just one more than the edge rank coloring number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Computing the minimum number of pebbles needed in Bennett's pebble game on an arbitrary DAG is PSPACE-complete; however, it is possible that the spooky pebble game's additional rules make reasoning about the game easier [18]. Previous work has found that applying Bennett's pebble game to a tree requires exactly one more pebble than the tree's edge rank coloring number, and complete trees with n nodes can be pebbled in n O(log log n) steps [19]. We are curious how much the spooky pebble game can improve on these bounds.…”
Section: Future Workmentioning
confidence: 99%
“…Computing the minimum number of pebbles needed in Bennett's pebble game on an arbitrary DAG is PSPACE-complete; however, it is possible that the spooky pebble game's additional rules make reasoning about the game easier [18]. Previous work has found that applying Bennett's pebble game to a tree requires exactly one more pebble than the tree's edge rank coloring number, and complete trees with n nodes can be pebbled in n O(log log n) steps [19]. We are curious how much the spooky pebble game can improve on these bounds.…”
Section: Future Workmentioning
confidence: 99%
“…If all predecessors of a pebbled vertex v contain pebbles, the pebble on v may be removed. Reversible pebblings have been studied in [43,39,38] and have been used to prove time-space trade-offs in reversible simulation of irreversible computation in [42,40,61,16]. In a different context, Potechin [52] implicitly used reversible pebbling to obtain lower bounds in monotone space complexity, with the connection made explicit in later works [24,31].…”
Section: Pebble Gamesmentioning
confidence: 99%
“…If the underlying graph G is a complete binary tree on n vertices such a polynomial bound is unfortunately not known. While it is known that the smallest number of pebbles required to pebble a binary tree of height h is given by S = log(h) + Θ(log * (h)), where log * denotes the iterated logarithm, to our knowledge the best upper bound on the number of steps is n O(log log(n)) , given in [21]. It is an open problem if a binary tree on n vertices can be pebbled with a polynomial number of steps provided that only S pebbles are available, where S is as above.…”
Section: Preliminariesmentioning
confidence: 99%
“…The pebble games we study are played on directed acylic graphs that have the structure of ternary trees. In related work [21] pebbling of other classes of trees has been considered, in particular that of complete binary trees.…”
Section: Introductionmentioning
confidence: 99%